IPTEK BAGI MASYARAKAT (IB.M) WIRAUSAHA BARU PEMUDA KARANG TARUNA DI DESA SANENREJO KECAMATAN TEMPUREJO KAB. JEMBER - Dimyati, Muhaimin; Sari, Nurshadrina Kartika (Universitas Muhammadiyah Jember, 2015)
Youth clubs are a group of youths in the village which was formed by the Ministry of Social operationally implemented by social services. Youth activity was limited to a positive use of leisure time such as recreation, sports, arts, scouting (scouts), religious education (teaching) and others for orphans, school dropouts, and no school. Currently, Youth has conducted various activities, in an effort to contribute to address the problem of Social Welfare, especially facing young people in their environment. In addition, the dropout rate increased in number every year. Unemployment in East Java reached 4.33% in 2013 increased by 0.21% compared to 2012. The village Sanenrejo a remote village forest edge Betiri Meru national park is about 42 km from the city with most of the damaged roads. In this village, in addition to many children dropping out of school, there are also many migrant workers and trafficking victims. Because employment in the village are very limited, just as forest farmers and farm workers, many people who become migrant workers abroad. Even though it is a remote area, motorists in the village Sanenrejo more and require treatment. In this village there are a field in front of the village hall which is used for recreation village park in the afternoon. With such conditions, it was attempted to take advantage of opportunities and opportunities to develop youth activities youth village Sanenrejo, who had only sporting activities and social, will be developed sector of Economical Productive which help create jobs for the unemployed and young school dropouts , by developing new entrepreneurship workshops and a food court. To achieve the expected outcomes, the methods of implementation are used, among other things: management and technical training, apprenticeship, mentoring, and monitoring and evaluation. Specifically required expertise in the field of mechanical engineering. It can be obtained from the UPT Latihan Kerja Disnakertrans Prop Jatim in Jember. There was also support from Jember Mandala STIE P3M performance that have earned awards from Kopertis Region VII East Java for his achievements in managing the Research and Community Service every year from 2008 to 2015.